Warfare & society in Europe : 1898 to the present - Neiberg, Michael S. (Warfare and history., 2004)
"Warfare and Society in Europe, 1898 to the Present examines Warfare in Europe from the Fashoda conflict in 1898 in modern-day Sudan to the recent war in Iraq. The twentieth century was by far the world's most destructive century, with two global wars marking the first half of the century and the constant fear of nuclear annihilation haunting the second half. Throughout, this book treats warfare as a function of large political, cultural, social and economic issues." "Combining a traditional survey of military history with a survey of social issues, Michael S. Neiberg examines both how social changes have impacted the nature of war fighting and how war has shaped the basic patterns of European society."--Jacket